Business advice by accountants to SMEs: relationships and trust. Issue 3 (6th August 2018) - Blackburn, Robert; Carey, Peter; Tanewski, George
Abstract : Purpose: The purpose of this paper is to test a conceptual framework explaining the role of relationships and trust in enabling the purchase of business advice by small business owner–managers from their external accountants. Design/methodology/approach: The study uses a semi-structured interview approach with 20 small- and medium-sized enterprise (SME) owners and accountants in London and Melbourne. Findings: The interview data support the conceptual framework's central proposition that relationships and trust, rather than being antecedents of demand for advice, are necessary conditions for enabling latent demand. SMEs with greater propensity to trust are more open to buying business advice but not necessarily from their accountant. Research limitations/implications: A limitation of the fieldwork is that it is based on a non-random and limited sample of accountants and SMEs. Practical implications: Accountants in public practice can no longer assume that the already established relationships with their clients, developed while providing compliance services, will automatically lead SME clients to purchase business advice. Originality/value: The paper contributes to the accounting literature by developing a conceptual model of relationships and trust that will assist the profession in better understanding the complex dynamics of the accountant–client relationship. The conceptual model distinguishes, for the first time, the antecedent factors of demand for business advice from the enabling roles of relationships and trust. Fieldwork interviews also yielded new insights into how SMEs' decisions to purchase business advice are influenced by specific personality traits of SME owner–managers and additional antecedent demand factors not identified in the extant literature – economic conditions, environmental turbulence and business life-cycle.